2022
DOI: 10.3389/fpsyg.2022.1051728
|View full text |Cite
|
Sign up to set email alerts
|

Exploring classroom-based assessment for young EFL learners in the Chinese context: Teachers’ beliefs and practices

Abstract: Classroom-based assessment (CBA) is an approach for learning improvement that has been advocated as having strong potential in enhancing learner autonomy of young language learners (YLLs). This study investigated Chinese primary school English as a foreign language (EFL) teachers’ beliefs about CBA, their assessment practices, and the relationship between their CBA beliefs and practices. Drawing on data from a survey of 195 Chinese primary school EFL teachers, results showed that the teachers positively believ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 89 publications
0
1
0
Order By: Relevance
“…Behaviours [27] and decision-making [28] in language learning are also complex and include different stages (e.g., before learning, during learning) and types of decision-making (e.g., choice of learning resources, learning methods). When user-generated content is shared through social networking applications, it often stimulates people's interest and motivation for language learning [29].…”
Section: Language Learning Through Social Mediamentioning
confidence: 99%
“…Behaviours [27] and decision-making [28] in language learning are also complex and include different stages (e.g., before learning, during learning) and types of decision-making (e.g., choice of learning resources, learning methods). When user-generated content is shared through social networking applications, it often stimulates people's interest and motivation for language learning [29].…”
Section: Language Learning Through Social Mediamentioning
confidence: 99%
“…The studies by Zhou and Deneen (2016) and Wu et al (2021) concluded that teachers' beliefs directly impact their instruction and lesson focus in EFL contexts. According to Yan et al (2022), teachers' beliefs can be predictors of their practices of L2 classroom assessment. Nevertheless, the studies by Vattoy (2020) and Wang et al (2020) indicated that L2 teachers' beliefs may not directly influence their practices of classroom assessment.…”
Section: Beliefs and Practices Regarding L2 Classroom Assessmentmentioning
confidence: 99%